Hukum Islam sebagai rekayasa sosial dan implikasinya dalam undang-undang perkawinan di Indonesia - Danu Aris Setiyanto (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
This study focuses on the role of Islamic law as social engineering and its implications in marriage law in Indonesia. Islamic law has always been a concern among legal experts and studies. One interesting thing is the effort to achieve justice through the application of Islamic law which functioned as social engineering. Though the nature of Islamic law is the dimension of social justice but at the same dimensions of the Godhead. In the Indonesian context, it is understood that the marriage law in Indonesia is the implication. As this study included the study of literature and research data analyzed by the theory of law as a social engineering with the sociological approach. The results of this study concluded Law Islamic law can function and formulated as social engineering in the form of state regulation and in fact it is contained in the articles of the Marriage Law in Indonesia.